Ecofeminism and Digital Environmental Activism: A Case Study of Climate Campaigns in Southeast Asia - Irfan Azis (Return : Study of Management, Economic and Bussines, 2025)
Climate change is becoming an increasingly urgent global issue, especially in the Southeast Asian region that is vulnerable to ecological disasters. In this context, ecofeminism offers a critical framework for understanding the relationship between domination of women and environmental exploitation. This study aims to analyze how ecofeminism values are represented in digital climate campaigns in Southeast Asia, as well as assess their impact on public awareness and environmental policies. This research uses a qualitative approach with a critical-feminist paradigm through comparative case studies in Indonesia, Thailand, and Vietnam. Data were obtained through analysis of digital content on social media (Instagram, Twitter/X, Facebook), in-depth interviews with women activists, and analysis of policy documents and academic literature. The analysis was carried out using a critical discourse analysis (AWK) approach to examine the construction of the narrative of ecofeminism in the digital space. The results show that ecofeminism-based digital campaigns, such as #Ibukudiatplastik and #ClimateStrikeSEA, have succeeded in increasing public awareness of the interconnectedness of gender and the environment, with the highest achievement in Indonesia, followed by Thailand and Vietnam. However, direct influence on policy is still limited, so digital activism is more effective in building collective awareness and strengthening women's political capacity than creating concrete regulatory changes. This study recommends the need to integrate digital strategies with formal policy advocacy, strengthening transnational networks of women activists, and improving people's digital-ecological literacy. Thus, digital ecofeminism can serve not only as an arena for discourse, but also as a transformative instrument in the struggle for ecological justice in Southeast Asia.